Steel material and automobile component
By optimizing the chemical composition and structure of the steel, increasing the content of Ni and Si, and forming a metal structure containing austenite phase and an ordered phase, the problem of difficulty in achieving high corrosion resistance and high manufacturing properties at the same time by optimizing the chemical composition and structure of the steel, the effect of high strength, high ductility and high corrosion resistance is achieved.
Patent Information
- Application Number
- CN202280099565.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-02
- Publication Date
- 2025-04-04
AI Technical Summary
While the existing third-generation AHSS steel meets the balance of high strength, high ductility and high strength ductility, it is difficult to achieve high corrosion resistance and high manufacturing properties at the same time.
By optimizing the chemical composition of the steel, the content of Ni and Si is increased, and the metal structure containing the austenite phase and the ordered phase is formed, while controlling the average crystal grain size and the presence of the reverse phase boundary of the ordered phase, satisfying the specific chemical composition ratio and structure structure.
It achieves a balance of high strength, high ductility and high strength ductility of steel, and significantly improves corrosion resistance and manufacturing properties, exceeding the current third-generation AHSS level.
Smart Images

Figure CN119768548A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to steel products and automobile parts. Background Art
[0002] In recent years, there has been a demand for steel materials with higher mechanical properties and higher functionality than general steel materials. To give an example, steel materials used in automobiles require both high strength and high ductility that can be formed according to the shape of the parts in order to reduce the weight of the vehicle body and improve safety performance. Depending on the location and environment of the component, high corrosion resistance is also required to extend its service life.
[0003] Steel materials with excellent balance between strength and ductility are called AHSS (Advanced High Strength Steel) and have been developed in the past.
[0004] The first generation AHSS represented by TRIP (Transformation-Induced Plasticity) steel has an insufficient balance between strength and ductility. In contrast, the second generation AHSS represented by high Mn steel has an excellent balance between strength and ductility, but the high Mn content is a factor that has prevented it from being effectively utilized.
[0005] In view of the development of the first and second generation AHSS, the development of the third generation AHSS represented by medium Mn steel has been active in recent years. The development examples of the third generation AHSS carried out in the past are described. It should be noted that "%" means mass %.
[0006] For example, Patent Document 1 discloses "a steel plate and a process for providing a steel plate, wherein the steel plate comprises a composition containing 3 to 8% Mn, 2 to 4% Al, 0.1 to 0.2% Si, 0.3 to 0.8% C and the remainder of iron and impurities, and comprises a ferrite phase, a bainite phase, an austenite phase, and a martensite phase."
[0007] Patent document 2 discloses "a steel plate and a process for providing a steel plate, wherein the steel plate has a composition comprising C: 0.1-0.4%, Mn: 1-3%, Si: 1-2%, Ti: 0.1-0.2% and the remainder of iron and impurities, and comprises a ferrite phase, a bainite phase, an austenite phase, and a martensite phase."
[0008] Patent document 3 discloses "a hot-rolled steel strip or steel plate comprising C: 0.12-0.24%, Mn: 0.8-2.1%, Si: 0.4-1.1%, Cr: 0.8-1.5%, Al: 0.05-0.3%, Mo: 0.05-0.25%, Nb: 0.018-0.035%, Ti: 0.01-0.1%, S: maximum 0.008%, P: maximum 0.025%, N: maximum 0.005%".
[0009] Patent Document 1: Japanese Patent Application Publication No. 2016-141888
[0010] Patent Document 2: Japanese Patent Application Publication No. 2016-223003
[0011] Patent Document 3: Japanese Patent Application No. 2020-514544 Summary of the invention
[0012] Problems to be solved by the invention
[0013] In Patent Documents 1 to 3, strength, ductility, and strength-ductility balance are obtained by including 0.8 to 8% of Mn and forming a complex structure into a non-ordered phase (ferrite, austenite, martensite, bainite, etc.).
[0014] However, the current situation of steel materials in recent years is that in addition to high strength, high ductility, and high strength-ductility balance at a level exceeding the current third generation AHSS (Current 3rd GENAHSS), high corrosion resistance and high manufacturability are also required.
[0015] Therefore, an object of the present disclosure is to provide a steel material having high strength, high ductility, and a high balance of strength and ductility at a level exceeding that of the current third-generation AHSS, and having high corrosion resistance and high manufacturability.
[0016] Means for solving problems
[0017] In order to solve the above problems, the inventors developed steel materials with a completely different technical concept from the past. As a result, the inventors found that it is effective to devise settings regarding the following points (A) to (C), and thus completed the invention.
[0018] (A) As an austenite stabilizing element, Ni is effectively utilized instead of Mn.
[0019] (B) A larger amount of Si is contained in the steel material than before.
[0020] (C) A metal structure containing an austenite phase and an ordered phase is produced.
[0021] Furthermore, the inventors have found that it is effective to implement any one of the following points (D) to (I) in order to solve the above-mentioned problems at a higher level, thereby completing the invention.
[0022] (D) The average chemical composition of the steel material satisfies the following formula A.
[0023] (E) The ordered phase includes a DO3 type ordered phase, and the ratio of the DO3 type ordered phase satisfies the following formula B.
[0024] (F) The average chemical composition of the ordered phase satisfies the following formula C.
[0025] (G) As the average chemical composition of the austenite phase, it satisfies the formula D described below.
[0026] (H) The average crystal grain size of the ordered phase is set to 10.00 μm or less.
[0027] (I) Contains antiphase boundaries in the ordered phase.
[0028] That is, means for solving the above-mentioned problems include the following.
[0029] <1> A steel material having the following average chemical composition in mass %:
[0030] Ni: 18.00~36.00%,
[0031] Si: 5.50-12.00%,
[0032] Cu: 0-2.00%,
[0033] Al: 0~3.000%,
[0034] Mn: 0-2.00%,
[0035] C: 0~0.100%,
[0036] Cr: 0~0.40%
[0037] P: 0~0.200%、
[0038] S: 0~0.200%,
[0039] N: 0~0.200%、
[0040] B: 0~0.200%,
[0041] Sn: 0~0.20%,
[0042] Ge: 0~0.20%
[0043] Ag: 0~0.20%,
[0044] Sb: 0~0.20%,
[0045] Te: 0~0.20%
[0046] V: 0~0.200%、
[0047] Nb: 0~0.200%,
[0048] Ti: 0~0.200%,
[0049] Ca: 0~0.200%,
[0050] Mg: 0~0.200%,
[0051] Li: 0~0.20%
[0052] Sr: 0~0.20%,
[0053] REM: 0~0.20%
[0054] Zr: 0~0.20%,
[0055] Co: 0~0.20%
[0056] Mo: 0~0.20%
[0057] Ta: 0~0.20%,
[0058] W: 0~0.20%,
[0059] PGM: 0~0.20%,
[0060] Au: 0~0.20%,
[0061] Re: 0~0.20%
[0062] In: 0~0.20%,
[0063] Ga: 0~0.20%,
[0064] Cd: 0~0.20%,
[0065] Pb: 0 to 0.20%, and
[0066] The rest: Fe and impurities,
[0067] Furthermore, it has a metal structure including an austenite phase and an ordered phase.
[0068] <2> according to <1> The steel material, wherein
[0069] The average chemical composition of the steel material satisfies the following formula A.
[0070] Type A: C+Mn / 6+Si / 24+Ni / 40+Cr / 5≤1.4
[0071] (In formula A, each element symbol represents the content (mass %) of the corresponding element.)
[0072] <3> according to <1> or <2> The steel material, wherein
[0073] The average area ratio of the austenite phase is within a range of 20 to 80%.
[0074] <4> according to <1> ~ <3> Any one of the steel materials, wherein
[0075] The ordered phase includes a DO3 type ordered phase, and the ratio of the DO3 type ordered phase to all ordered phases ([DO3 type ordered phase] / [all ordered phases]) determined by X-ray diffraction satisfies the following formula B.
[0076] Formula B: [DO3 type ordered phase] / [all ordered phases]≥0.20
[0077] <5> according to <1> ~ <4> Any one of the steel materials, wherein
[0078] The average chemical composition of the ordered phase satisfies the following formula C.
[0079] Formula C: (Si ordered +Al ordered ) / (Ni ordered +Cu ordered )≥0.25
[0080] (In formula C, the symbols of each element ordered This symbol represents the content (mass %) of the corresponding element in the ordered phase.
[0081] <6> according to <1> ~ <5> Any one of the steel materials, wherein
[0082] The average chemical composition of the austenite phase satisfies the following formula D.
[0083] D type:Ni γ +0.65Cr γ +1.1Mn γ +0.4Si γ +13C γ ≥18.4(D In the formula, the symbol of each element γ This symbol indicates the content (mass %) of the corresponding element in the austenite phase.
[0084] <7> according to <1> ~ <6> Any one of the steel materials, wherein
[0085] The average crystal grain size of the ordered phase is 10.00 μm or less.
[0086] <8> according to <1> ~ <7> Any one of the steel materials, wherein
[0087] The above-mentioned ordered phase contains an antiphase boundary.
[0088] <9> according to <1> ~ <8> The steel material described in any one of the above aspects has a product of tensile strength and total elongation of 30000 MPa% or more.
[0089] <10> according to <1> ~ <9> Any one of the steel materials, wherein
[0090] The tensile strength is above 1250 MPa.
[0091] <11> An automobile component,
[0092] It has <1> ~ <10> The steel material described in any one of the above.
[0093] Effects of the Invention
[0094] According to the present disclosure, it is possible to provide a steel material having high strength, high ductility, and a high balance of strength and ductility at a level exceeding that of the current third-generation AHSS, and having high corrosion resistance and high manufacturability. BRIEF DESCRIPTION OF THE DRAWINGS
[0095] Figure 1 This is an example of an optical microscope photograph of the metal structure of the steel material of the present disclosure of Test No. 35 after hot rolling annealing and before finish annealing (magnification 500 times, white portion is γ phase, gray portion is ordered phase).
[0096] Figure 2 This is an example of an optical microscope photograph of the metal structure of the steel material of the present disclosure of Test No. 36 (magnification 500 times, white portion is γ phase, gray portion is ordered phase). DETAILED DESCRIPTION
[0097] Hereinafter, an example of the present disclosure will be described.
[0098] In addition, in this disclosure, "%" indicating the content of each element in the chemical composition means "mass %".
[0099] The numerical range expressed using "to" means a range including the numerical values described before and after "to" as the lower limit and the upper limit.
[0100] The term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.
[0101] “Ferrite” is also described as “α”, and “austenite” is also described as “γ”.
[0102] <<<Steel>>>
[0103] The steel material disclosed herein has a predetermined average chemical composition and a metal structure including an austenite phase and an ordered phase.
[0104] The steel material disclosed in the present invention has the above-mentioned structure and has high strength, high ductility, and a high strength-ductility balance at a level exceeding that of the current third-generation AHSS, and has high corrosion resistance and high manufacturability.
[0105] Furthermore, the steel material of the present disclosure was discovered through the following findings.
[0106] The inventors conducted research focusing on the chemical composition of steel materials in order to improve the strength, ductility, and strength-ductility balance of steel materials as well as the corrosion resistance and manufacturability. As a result, the inventors obtained the following findings.
[0107] As the main chemical composition of the steel, by containing 18.00-36.00% Ni, 5.50-12.00% Si, and setting the amount of optional elements other than Ni and Si described later to a prescribed amount or less (especially setting the amount of Al and Mn to a prescribed amount or less), a metal structure containing a γ phase and an ordered phase is formed. By making the relatively soft γ phase that helps improve ductility and the hard ordered phase that helps improve strength coexist in the metal structure, the strength, ductility and strength-ductility balance of the steel are improved. However, if the amount of optional elements other than Ni and Si described later becomes excessive, the strength or ductility deteriorates.
[0108] Furthermore, by containing a large amount of Si in the steel material, the corrosion resistance of the steel material is also improved.
[0109] It should be noted that, in general, if 5.50 to 12.00% Si is contained, the steel becomes brittle, and hot working and cold working become difficult. However, when Ni is sufficiently contained and the γ phase and the ordered phase coexist, the brittleness of the steel can be suppressed, and the commonly used hot working and cold working can be performed, and the manufacturability is improved. However, if the amount of Si is excessive or the amount of Ni becomes too small, the manufacturability deteriorates.
[0110] Based on the above findings, it was found that the steel material disclosed in the present invention has high strength, high ductility, and a high strength-ductility balance at a level exceeding that of the current third-generation AHSS, and has high corrosion resistance and high manufacturability.
[0111] Hereinafter, the steel material of the present disclosure will be described in detail.
[0112] <<Average Chemical Composition of Steel>>
[0113] Hereinafter, the average chemical composition of the steel material of the present disclosure will be described.
[0114] <Ni:18.00~36.00%>
[0115] Ni contributes to the improvement of ductility and strength-ductility balance. Ni is a γ-stabilizing element, and by being contained in the steel, the γ phase is stabilized. The γ phase is relatively superior in ductility compared to the ordered phase. Moreover, by including the γ phase in the steel, the ductility and strength-ductility balance are improved. Such an effect is significantly manifested when the Ni content is 18.00% or more. If the Ni content is too little, the stability of the γ phase is insufficient, so cracks occur in the manufacturing process, the ductility of the steel becomes insufficient, and the strength-ductility balance also becomes insufficient.
[0116] If the Ni content is too high, not only will the manufacturability be adversely affected and cracks will occur during the manufacturing process, but also an ordered phase that contributes to improving the strength will not be sufficiently formed.
[0117] Therefore, the Ni content is 18.00 to 36.00%.
[0118] The lower limit of the Ni content is preferably 20.00%, more preferably 22.00%.
[0119] The upper limit of the Ni content is preferably 32.00%, more preferably 30.00%.
[0120] <Si:5.50~12.00%>
[0121] Si contributes to the improvement of strength, strength-ductility balance and corrosion resistance. If a lot of Si is contained in Fe, the α phase is ordered. In the case where the steel is composed of a metal structure of an ordered phase in which only the α phase is ordered, the steel becomes brittle and is difficult to use in industry. However, in the case of containing both the γ phase and the ordered phase, the brittleness of the steel can be suppressed and it has sufficient ductility. The ordered phase is harder than the γ phase and contributes to the improvement of strength. In addition, by containing Si, a protective layer containing Si oxide with excellent corrosion resistance is formed on the surface of the steel. Therefore, the inclusion of Si is effective for improving corrosion resistance. These effects are manifested when the Si content is 5.50% or more. If the amount of Si is too little, the ordering of the α phase is insufficient, so the formation of the ordered phase is insufficient, the strength of the steel becomes insufficient, and the strength-ductility balance becomes insufficient. In addition, the formation of the Si oxide layer that functions as a protective layer on the surface of the steel also becomes insufficient, and the improvement of corrosion resistance also becomes insufficient.
[0122] If the Si content is too high, cracking occurs during the manufacturing process, the ductility of the steel material becomes insufficient, and the strength-ductility balance also becomes insufficient.
[0123] Therefore, the Si content is 5.50 to 12.00%.
[0124] The lower limit of the Si content is preferably 6.50%, more preferably 8.00%.
[0125] The upper limit of the Si content is preferably 10.00%, more preferably 9.50%.
[0126] <Cu:0~2.00%>
[0127] Cu is an optional element.
[0128] Cu has the same effect as Ni in stabilizing the γ phase and improving ductility and strength-ductility balance. Cu has a smaller amount of atoms that can be dissolved in the γ phase than Ni, and excessive Cu content causes Cu precipitation, which reduces ductility and manufacturability.
[0129] Therefore, the content of Cu is 0 to 2.00%.
[0130] The lower limit of the Cu content is preferably 0.20%.
[0131] The upper limit of the Cu content is preferably 1.50%.
[0132] <Al:0~3.000%>
[0133] Al is an optional element.
[0134] Al, like Si, has the effect of ordering the α phase and improving the balance between strength and strength-ductility. It should be noted that even if Al is contained, there is no effect of improving corrosion resistance. On the other hand, excessive Al content will reduce the Si solid solubility limit in steel. In addition, excessive Al content will hinder the formation of ordered phases (specifically, B2-type ordered phases with FeSi as the basic chemical composition and DO3-type ordered phases with Fe3Si as the basic chemical composition), which will also have an adverse effect on corrosion resistance.
[0135] Therefore, the Al content is 0 to 3.000%.
[0136] The lower limit of the Al content is preferably 0.002%, 0.005%, 0.010%, or 0.100%.
[0137] The upper limit of the Al content is preferably 2.700%, 2.000%, 1.500%, or 1.000%.
[0138] <Mn:0~2.00%>
[0139] Mn is an optional element.
[0140] Mn, like Ni and Cu, has the effect of stabilizing the γ phase and improving the balance of ductility and strength ductility. On the other hand, Mn has no particular effect on corrosion resistance, and the formation of MnS caused by excessive Mn content will deteriorate the corrosion resistance.
[0141] Therefore, the content of Mn is 0 to 2.00%.
[0142] The lower limit of the content of Mn is preferably 0.02%, 0.05%, or 0.10%.
[0143] The upper limit of the content of Mn is preferably 1.60%, 1.40%, or 1.00%.
[0144] <C: 0 to 0.100%>
[0145] C is an optional element.
[0146] C, like Ni, has the effect of stabilizing the γ phase and improving the balance of ductility and strength ductility. On the other hand, excessive C content will promote the formation of coarse Fe carbides and cause cracking in the manufacturing process.
[0147] Therefore, the content of C is set to 0 to 0.100%.
[0148] Since it is difficult to set the content of C to 0%, the lower limit of the content of C is preferably 0.001%, 0.005%, or 0.010%.
[0149] The upper limit of the content of C is preferably 0.085%, 0.075%, or 0.060%.
[0150] <Cr: 0 to 0.40%>
[0151] Cr is an optional element.
[0152] Cr has the effect of inhibiting the occurrence of corrosion at the inclusion initiation point. On the other hand, excessive Cr content will be a cause of brittle fracture.
[0153] Therefore, the content of Cr is 0 to 0.40%.
[0154] The lower limit of the content of Cr is preferably 0.01%.
[0155] The upper limit of the content of Cr is preferably 0.35%.
[0156] <P and S: 0 to 0.200%>
[0157] P and S are impurities that will reduce the toughness of the steel.
[0158] Therefore, the contents of P and S are 0 to 0.200% respectively.
[0159] The less the contents of P and S are, the more preferable. However, from the viewpoint of the cost of P and S removal, they can also be 0.001% or more.
[0160] <N and B: 0 to 0.200%>
[0161] N and B are optional elements.
[0162] N and B are solution strengthening elements and have the effect of contributing to the improvement of strength. In addition, N and B can also be effectively used for the control of pinning particles and inclusions. On the other hand, the inclusion of excessive N and B will form nitrides or borides that are larger than necessary and become a factor in the reduction of ductility.
[0163] Therefore, the contents of N and B are 0 to 0.200% respectively.
[0164] The lower limits of the contents of N and B are preferably 0.001% respectively.
[0165] The upper limits of the contents of N and B are preferably 0.150% respectively.
[0166] <Sn, Ge, Ag, Sb and Te: 0 to 0.20%>
[0167] Sn, Ge, Ag, Sb and Te are optional elements.
[0168] Sn, Ge, Ag, Sb and Te have the effect of contributing to the improvement of corrosion resistance. On the other hand, the inclusion of excessive Sn, Ge, Ag, Sb and Te will become a factor in the embrittlement of the material and the reduction of manufacturability.
[0169] Therefore, the contents of Sn, Ge, Ag, Sb and Te are 0 to 0.20% respectively.
[0170] The lower limits of the contents of Sn, Ge, Ag, Sb and Te are preferably 0.01% respectively.
[0171] The upper limits of the contents of Sn, Ge, Ag, Sb and Te are preferably 0.18% respectively.
[0172] <V, Nb and Ti: 0 to 0.200%>
[0173] V, Nb and Ti are optional elements.
[0174] V, Nb and Ti have the effect of refining crystal grains by forming carbonitrides, etc. Ti also functions as a deoxidizing element. On the other hand, the inclusion of excessive V, Nb and Ti will cause cracking during casting and solidification due to the segregation of these elements and become a reason for the reduction of manufacturability.
[0175] Therefore, the contents of V, Nb and Ti are 0 to 0.200% respectively.
[0176] The lower limits of the contents of V, Nb and Ti are preferably 0.001% respectively.
[0177] The upper limits of the contents of V, Nb and Ti are preferably 0.080% respectively.
[0178] <Ca and Mg: 0 to 0.200%>
[0179] Ca and Mg are optional elements.
[0180] Ca and Mg have the effect of modifying the metal structure of the ingot and suppressing cracking during casting by forming inclusions such as oxides and sulfides, thereby improving manufacturability. On the other hand, the inclusion of excessive Ca and Mg becomes a cause of cracks and cracking during manufacturing due to an increase in the number, size, volume fraction, etc. of the inclusions.
[0181] Therefore, the contents of Ca and Mg are 0 to 0.200% respectively.
[0182] The lower limits of the contents of Ca and Mg are preferably 0.001% respectively.
[0183] The upper limits of the contents of Ca and Mg are preferably 0.150% respectively.
[0184] <Li, Sr, REM and Zr: 0 to 0.20%>
[0185] Li, Sr, REM and Zr are optional elements.
[0186] Li, Sr, REM and Zr have the effect of contributing to the improvement of oxidation resistance. On the other hand, by containing excessive Li, Sr, REM and Zr, no further improvement in oxidation resistance can be obtained, and only the raw material cost is increased.
[0187] Therefore, the contents of Li, Sr, REM and Zr are 0 to 0.20% respectively.
[0188] The lower limits of the contents of Li, Sr, REM and Zr are preferably 0.01% respectively.
[0189] The upper limits of the contents of Li, Sr, REM and Zr are preferably 0.18% respectively.
[0190] Here, REM (rare earth elements) refers to the general term for 2 elements, Sc and Y, and 15 elements of the lanthanide series such as La, Ce and Nd. REM is composed of one or more selected from these rare earth elements, and the content of REM is the sum of the contents of the rare earth elements.
[0191] <Co: 0 to 0.20%>
[0192] Co is an optional element.
[0193] Co has the effect of contributing to the improvement of toughness. In addition, it also has the effect of stabilizing the γ phase. On the other hand, the inclusion of excessive Co will cause the corrosion resistance of the ordered phase to deteriorate or the toughness of the steel itself to deteriorate.
[0194] Therefore, the content of Co is 0 to 0.20% respectively.
[0195] The lower limit of the content of Co is preferably 0.01% respectively.
[0196] The upper limit of the content of Co is preferably 0.18% respectively.
[0197] <Mo, Ta, W, PGM, Au and Re: 0 to 0.20%>
[0198] Mo, Ta, W, PGM, Au and Re are optional elements.
[0199] Mo, Ta, W, PGM, Au and Re have the effect of contributing to the improvement of corrosion resistance. On the other hand, the inclusion of excessive Mo, Ta, W, PGM, Au and Re will cause the ductility of the steel itself to deteriorate due to the reduction of the ductility of the ordered phase.
[0200] Therefore, the content of Mo, Ta, W, PGM, Au and Re is 0 to 0.20% respectively.
[0201] The lower limit of the content of Mo, Ta, W, PGM, Au and Re is preferably 0.01% respectively.
[0202] The upper limit of the content of Mo, Ta, W, PGM, Au and Re is preferably 0.19% respectively.
[0203] Here, PGM (platinum group elements) refers to the general term for the six elements of Pt, Pd, Ru, Ir, Os, and Rh. PGM is composed of one or more selected from these platinum group elements, and the content of PGM is the sum of the contents of the platinum group elements.
[0204] <In, Ga, Cd and Pb: 0 to 0.20%>
[0205] In, Ga, Cd and Pb are optional elements.
[0206] In, Ga, Cd and Pb have the effect of contributing to the improvement of corrosion resistance. On the other hand, the inclusion of excessive In, Ga, Cd and Pb will cause the toughness to decrease and the manufacturability to deteriorate.
[0207] Therefore, the contents of In, Ga, Cd, and Pb are 0 to 0.20% respectively.
[0208] The lower limits of the contents of In, Ga, Cd, and Pb are preferably 0.01% respectively.
[0209] The upper limits of the contents of In, Ga, Cd, and Pb are preferably 0.19% respectively.
[0210] <The remaining part>
[0211] The remaining part of the average chemical composition of the steel of the present disclosure is Fe and impurities.
[0212] Impurities refer to components mixed in during the industrial manufacturing of steel due to raw materials such as ores and scrap iron, and other factors.
[0213] <Formula A>
[0214] In the case of more strictly controlling cracks and cracking during hot working and cold working, it is preferable to further limit the balance of elements contained in the steel. Specifically, in addition to limiting the main contained elements, namely Ni and Si, it is also preferable to limit other elements contained in the steel.
[0215] Therefore, from the viewpoint of suppressing cracks and cracking, the chemical composition of the steel of the present disclosure preferably satisfies the following Formula A.
[0216] Formula A: C + Mn / 6 + Si / 24 + Ni / 40 + Cr / 5 ≤ 1.4
[0217] (In Formula A, each element symbol represents the content (mass %) of the corresponding element.)
[0218] The upper limit of the value of "C + Mn / 6 + Si / 24 + Ni / 40 + Cr / 5" in Formula A (hereinafter also referred to as the "A value") is more preferably 1.3, and further preferably 1.0.
[0219] The lower limit of the A value in Formula A is more preferably 0.6, and further preferably 0.8.
[0220] <<Metallographic structure>>
[0221] The metallographic structure of the steel of the present disclosure includes a γ phase and an ordered phase.
[0222] In order to obtain a steel containing a γ phase and an ordered phase, Si and Ni are contained in the above ranges, and the amounts of optional elements other than Ni and Si are contained below a specified amount.
[0223] In the case where only Si among Ni and Si is contained in Fe, although the corrosion resistance is excellent, the steel itself becomes brittle and processing becomes difficult, so industrial utilization is also difficult.
[0224] On the other hand, when Ni is contained in Fe or only Ni is contained in Si, sufficient ductility is exhibited, but sufficient strength, strength-ductility balance, and corrosion resistance are not exhibited.
[0225] By containing both Si and Ni within the above-mentioned suitable range and containing an amount of optional elements other than Ni and Si at a predetermined amount or less, a steel material including a γ phase and an ordered phase can be obtained.
[0226] <Average area ratio of γ phase: 20 to 80%>
[0227] The steel material disclosed herein preferably has an average area ratio of the γ phase of 20 to 80%.
[0228] By including the γ phase and the ordered phase, high strength, high ductility and high strength-ductility balance are achieved, and high corrosion resistance is achieved. On the other hand, if the average area ratio of the γ phase is within the range of 20 to 80%, strength, ductility and strength-ductility balance are further improved.
[0229] The γ phase takes on the strain caused by plastic deformation instead of the hard ordered phase contained in the steel material, thereby improving the ductility of the steel material, and as a result, the strength-ductility balance is also improved.
[0230] When the average area ratio of the γ phase is 20% or more, the γ phase, which is a region that bears plastic deformation, is present appropriately, and excessive introduction of strain due to plastic deformation into the ordered phase is suppressed, thereby further improving ductility.
[0231] On the other hand, when the average area ratio of the γ phase is 80% or less, sufficient ductility is improved, and the strain due to plastic deformation is suppressed from being excessively introduced into the ordered phase that contributes to strength improvement, thereby further improving strength and strength-ductility balance.
[0232] Therefore, in order to more optimally exert strength, ductility, and strength-ductility balance, the average area ratio of the γ phase is preferably 20 to 80%.
[0233] The average area ratio of the γ phase is more preferably 30 to 70%, further preferably 40 to 60%.
[0234] Here, the average area ratio of the ordered phase is set to the average area ratio of the metal structure other than the γ phase. That is, in the metal structure, the remaining part other than the γ phase is the ordered phase.
[0235] <Method for measuring the average area ratio of the γ phase>
[0236] When the steel material is a steel plate, the average area ratio of the γ phase is measured as follows.
[0237] Mirror-polish the L-section (a section cut along the rolling direction and the thickness direction) and the T-section (a section cut along the orthogonal direction and the thickness direction with respect to the rolling direction) of the steel plate. Corrode the mirror-polished surface with an oxalic acid aqueous solution with a concentration of 10% to color the γ-phase white and the ordered phase gray. Thus, prepare a test piece with the polished surface as the observation surface.
[0238] After that, when the average grain size of the ordered phase is 5.00 μm or more, observe the central part of the thickness of the test piece cross-section with an optical microscope at a magnification of 500 times. When the average grain size of the ordered phase is less than 5.00 μm, observe the central part of the thickness of the test piece cross-section with a scanning electron microscope at a magnification of 1000 times. By performing image analysis on them, calculate the area ratio of the γ-phase. For a total of 10 fields of view including 5 or more fields of view of the L-section and 5 fields of view of the T-section of the steel plate, calculate the area ratio of the γ-phase for each of them, and take their arithmetic mean value as the average area ratio of the γ-phase.
[0239] It should be noted that when the steel material is steel wire, bar steel or steel pipe, the measurement of the area ratio of the γ-phase is carried out by preparing a test piece with their longitudinal section and cross-section replacing the L-section and T-section as the observation surface. When the steel material is steel wire and bar steel, the observation part using the optical microscope is set to the part corresponding to the center of the diameter of the steel wire and bar steel in the test piece cross-section. When the steel material is steel pipe, the observation part using the optical microscope is set to the central part of the thickness of the test piece cross-section.
[0240] In addition, when the steel material is steel strip, section steel or foil, the measurement of the area ratio of the γ-phase is carried out in the same manner as in the case of steel plate.
[0241] <Ratio of DO3-type ordered phase>
[0242] Among the ordered phases, there are B2-type ordered phases with FeSi as the basic chemical composition and DO3-type ordered phases with Fe3Si as the basic chemical composition. Compared with the B2-type ordered phase, the DO3-type ordered phase has more excellent improvement in high strength and the balance of strength and ductility.
[0243] Therefore, it is preferable to increase the proportion of the DO3-type ordered phase. Specifically, the ordered phase contains the DO3-type ordered phase, and the ratio of the DO3-type ordered phase to all ordered phases obtained by X-ray diffraction preferably satisfies the following formula B. By the ratio of the DO3-type ordered phase satisfying the following formula B, the balance of strength and strength and ductility is further improved.
[0244] Formula B: [DO3-type ordered phase] / [all ordered phases] ≥ 0.20
[0245] It should be noted that all ordered phases are DO3-type ordered phases and B2-type ordered phases.
[0246] The lower limit of the value of "[DO3-type ordered phase] / [all ordered phases]" in the B formula (hereinafter also referred to as "B value") is more preferably 0.25, and further preferably 0.30.
[0247] The upper limit of the B value in the B formula is preferably 1.00, more preferably 0.91.
[0248] It should be noted that, similar to the existence of various compounds within a certain range of composition ratios, even if the ordered phase is a B2 type ordered phase, the ratio of Fe atoms to Si atoms (Fe atoms / Si atoms) is not completely limited to 1 / 1, and includes the range of 1 / 0.3 to 1 / 1.3; even if it is a DO3 type ordered phase, the ratio of Fe atoms to Si atoms (Fe atoms / Si atoms) is not completely limited to 3 / 1, and includes the range of 3 / 0.5 to 3 / 1.4.
[0249] In order to make the ratio of the DO3-type ordered phase satisfy the formula B, it is preferred to control the finish annealing temperature and the cooling rate after the finish annealing.
[0250] Specifically, the finish annealing temperature is preferably 600 to 1150° C., and the cooling rate after the finish annealing is preferably 0.010 to 10.000° C. / s.
[0251] Here, the annealing temperature refers to the surface temperature of the steel material.
[0252] The cooling rate after the finish annealing is an average cooling rate obtained by dividing the temperature difference between the finish annealing temperature and 400°C by the time required for cooling from the finish annealing temperature to 400°C.
[0253] <Method for determining the type of ordered phase and the ratio of DO3-type ordered phase>
[0254] When the steel material is a steel plate, the type of ordered phase and the ratio of the DO3 type ordered phase (B value of the B formula) are measured as follows.
[0255] The kind of ordered phase and the ratio of the DO3 type ordered phase were measured by XRD (X-ray diffraction).
[0256] The conditions for X-ray diffraction were to use CoKα rays as characteristic X-rays, set the voltage to 30 kV, and set the current to 100 mA. The measurement range of X-ray diffraction was set to 10°≤2θ≤110°, the step size was set to 0.04°, and the accumulation time was set to 2 s, and XRD measurement was performed by the θ-2θ method.
[0257] XRD was performed using a test piece (20 mm in length and 20 mm in width) whose surface was ground to half the thickness of the original plate as the observation surface, and the B2-type ordered phase and the DO3-type ordered phase were identified as ordered phases by the position of the obtained X-ray diffraction peaks. When the diffraction peak intensity was below the background, it was judged that it was not detected, and the area ratio of the corresponding phase was set to 0%.
[0258] The ratio of the DO3-type ordered phase, i.e., the B value of the B formula ([DO3-type ordered phase] / [all ordered phases]) is calculated from the data measured by XRD. The measurement is performed using CoKα radiation in the range of 2θ of 10 to 110°, and the obtained information is processed by the following method to calculate the B value of the B formula.
[0259] The B value of the B formula is calculated by converting the measured X-ray integrated intensity and intensity ratio into the diffraction intensity of a specific crystal lattice plane and calculating and comparing them from the average of the sum.
[0260] The calculation method is described below. It should be noted that DO3 type Fe3Si (220) and B2 type FeSi (210) .
[0261] In DO3 type Fe3Si, the integrated intensities of the nine diffraction planes (111)(200)(220)(311)(222)(400)(331)(420)(422) are converted into the integrated intensity of DO3 type Fe3Si(220).
[0262] In B2 type FeSi, the integrated intensities of the nine diffraction planes (110)(111)(200)(210)(211)(311)(023)(123)(400) are converted into the integrated intensity of B2 type FeSi(210).
[0263] It should be noted that the numerical values in () are the Miller indices (hkl) of the crystal. The B value of the B formula is calculated from the following formula using the measured integrated intensity and intensity ratio in the 2θ range. Specifically, it is as follows.
[0264] First, the integrated intensity and intensity ratio of the above diffraction surface are substituted into the following formula to calculate I B2 and I DO3 .
[0265] Formula: I B2 ={Σ(I B2(hkl) / R B2(hkl) )} / n
[0266] n=9
[0267] IB2(hkl) is the measured integrated intensity
[0268] R B2(hkl) To R B2(210) The intensity ratio is set to 1.
[0269] Formula: I DO3 ={Σ(I DO3(hkl) / R DO3(hkl) )} / n
[0270] n=9
[0271] I DO3(hkl) is the measured integrated intensity
[0272] R DO3(hkl) To R DO3(220) The intensity ratio is set to 1.
[0273] Next, using the calculated I B2 and I DO3 , calculate the B value of formula B by the following formula.
[0274] B value of formula B = I DO3 / (I B2 +I DO3 )
[0275] These operations were performed at 10 locations in the center of the steel sheet in the direction perpendicular to the rolling direction, and the arithmetic mean value was taken as the B value of the B formula.
[0276] It should be noted that when the steel material is a steel wire or a steel bar, the type of ordered phase and the ratio of the DO3 type ordered phase are measured by preparing a test piece with the surface ground from the radial direction of the steel wire or the steel bar to half the diameter of the steel wire or the steel bar as the observation surface.
[0277] When the steel material is a steel pipe, the type of ordered phase and the ratio of the DO3 type ordered phase are measured by preparing a test piece with a surface ground from the radial direction of the steel pipe to half the plate thickness of the steel pipe as the observation surface.
[0278] When the steel material is a steel strip, a steel shape, or a foil, the type of ordered phase and the ratio of the DO3 type ordered phase are measured in the same manner as when the steel material is a steel plate.
[0279] <Average chemical composition of the ordered phase>
[0280] The ordered phase is either a B2-type ordered phase or a DO3-type ordered phase, and Si, which is an α-phase stabilizing element, is preferably distributed in large quantities in the ordered phase. In addition, Si is an element effective in improving corrosion resistance, and it is preferred that more Si effective in improving corrosion resistance is distributed in the ordered phase that becomes a preferred anode in the corrosion reaction compared to the γ phase.
[0281] Specifically, the average chemical composition of the ordered phase preferably satisfies the following formula C.
[0282] In the corrosion reaction, the ordered phase becomes a preferential anode compared to the γ phase, but its behavior is significant when the Ni and Cu in the ordered phase are small, and becomes significant when the Si and Al in the ordered phase are large. In order to improve the corrosion resistance of the steel material, the ordered phase needs to be the preferential anode, and the Ni and Cu in the ordered phase are preferably small, and the Si and Al are preferably large. In particular, the Si in the ordered phase is preferably large in order to improve the corrosion resistance of the ordered phase itself.
[0283] Formula C is a formula expressing these relationships.
[0284] Therefore, when the average chemical composition of the ordered phase satisfies the following formula C, the corrosion resistance is further improved.
[0285] Formula C: (Si ordered +Al ordered ) / (Ni ordered +Cu ordered )≥0.25
[0286] (In formula C, the symbols of each element ordered This symbol represents the content (mass %) of the corresponding element in the ordered phase.
[0287] In formula C, "(Si ordered +Al ordered ) / (Ni ordered +Cu ordered The lower limit of the "C value" (hereinafter also referred to as "C value") is more preferably 0.29, and further preferably 0.39.
[0288] The upper limit of the C value in the C formula is more preferably 0.98, further preferably 0.88.
[0289] In order to make the average chemical composition of the ordered phase satisfy Formula C, it is preferred to control the finish annealing temperature and the soaking holding time at the finish annealing temperature.
[0290] Specifically, the finish annealing temperature is preferably 600 to 1150° C., and the soaking holding time at the finish annealing temperature preferably satisfies the following formula 1. If the following formula 1 is satisfied, the diffusion migration of atoms between the ordered phase and the γ phase proceeds sufficiently, so that the average chemical composition of the ordered phase satisfies the formula C.
[0291] Formula 1: 100×t 0.5 / T≥0.87
[0292] (In formula 1, t represents the soaking time (sec), and T represents the finished annealing temperature (°C).)
[0293] Here, the soaking holding time is the time from when the target finish annealing temperature is reached to when cooling starts.
[0294] <Average Chemical Composition of γ Phase>
[0295] The average chemical composition of the γ phase preferably affects the ductility and the strength-ductility balance and does not impair the ductility and strength-ductility balance.
[0296] Specifically, the average chemical composition of the γ phase preferably satisfies the following formula D. When the average chemical composition of the γ phase satisfies the following formula D, the ductility and strength-ductility balance of the γ phase are further improved, and the ductility and strength-ductility balance of the steel material itself can be improved.
[0297] D type:Ni γ +0.65Cr γ +1.1Mn γ +0.4Si γ +13C γ ≥18.4(D In the formula, the symbol of each element γ This symbol indicates the content (mass %) of the corresponding element in the γ phase.
[0298] The "Ni" in D γ +0.65Cr γ +1.1Mn γ +0.4Si γ +13C γ The lower limit of the "D value" (hereinafter also referred to as "D value") is more preferably 18.7, and further preferably 22.2.
[0299] The upper limit of the D value in the D formula is preferably 39.5, more preferably 37.0.
[0300] In order to make the average chemical composition of the γ phase satisfy the D formula, it is preferable to control the finish annealing temperature and the soaking holding time at the finish annealing temperature.
[0301] Specifically, the finish annealing temperature is preferably 600 to 1150° C., and the soaking holding time at the finish annealing temperature preferably satisfies the following equation 2. If the following equation 2 is satisfied, the diffusion migration of atoms between the ordered phase and the γ phase proceeds sufficiently, so that the average chemical composition of the γ phase satisfies equation D.
[0302] Formula 2: 500 × t0.5 / T≥1.77
[0303] (In formula 2, t represents the soaking time (sec), and T represents the annealing temperature of the finished product (°C).)
[0304] <Average chemical composition of γ phase and ordered phase>
[0305] When the steel material is a steel plate, the average chemical compositions of the γ phase and the ordered phase are measured as follows.
[0306] The L section and T section of the steel plate were mirror-polished to obtain a test piece. The central portion of the thickness of the steel plate section in the test piece was observed with a scanning electron microscope at a magnification of 1000 times when the average particle size of the ordered phase was 5.00 μm or more, and at a magnification of 2000 times when the average particle size of the ordered phase was less than 5.00 μm, and elemental analysis was performed using an EPMA (Electron Probe Micro Analyzer) attached to the scanning electron microscope to determine the average chemical composition of the γ phase and the ordered phase.
[0307] The analysis of the average chemical composition of the ordered phase is carried out as follows. Using an image magnified 3000 times the observation surface, a surface analysis is performed in an area of 30μm×30μm to determine the ordered phase. At this time, the ordered phase with an average crystal grain size of 0.5μm or more is taken as the object of determination. For the determined ordered phases, 10 ordered phases are selected in sequence from the ordered phase with the largest grain size, and the chemical composition in the center of the grain (the center of the largest radial direction of the grain) of these 10 ordered phases is analyzed by the EPMA method. The element to be measured by the EPMA method is set to an element represented by the average chemical composition of the steel disclosed in the present invention.
[0308] Then, for one field of view to be measured, the mass % of each element to be measured in the ordered phase is determined. The mass % of the element to be measured in the 10 ordered phases to be measured is substituted into the C value of the C formula ((Si ordered +Al ordered ) / (Ni ordered +Cu ordered )), the C values of each C formula are arithmetic averaged to calculate the representative value of the C value of the C formula in each field of view.
[0309] This operation is performed on a total of 10 viewing fields, including 5 viewing fields of the L section and 5 viewing fields of the T section. The representative value of the C value of the C formula obtained in each viewing field is further arithmetic averaged by the number of viewing fields, and the overall arithmetic mean value obtained is used as the representative value of the C value of the C formula of the steel plate.
[0310] The analysis of the average chemical composition of the γ phase is carried out in the same manner as the analysis of the average chemical composition of the ordered phase, except that the target phase is the γ phase instead of the ordered phase. Thus, the mass % of each element to be measured in the γ phase is determined to obtain a representative value of the D value of the D formula.
[0311] Here, in the EPMA method, the acceleration voltage is set to 15 KeV for measurement. By measuring by EPMA under such conditions, it is possible to perform point analysis on a region where one point is approximately 0.2 to 0.5 μm.
[0312] It should be noted that, when the steel material is a steel wire, a steel bar or a steel pipe, the average chemical composition of the γ phase and the ordered phase is measured by preparing a test piece with their longitudinal section and cross section as the observation surface instead of the L section and the T section. When the steel material is a steel wire or a steel bar, the observation portion using a scanning electron microscope is set to a portion corresponding to the central portion of the diameter of the steel wire or the steel bar in the cross section of the test piece. When the steel material is a steel pipe, the observation portion using a scanning electron microscope is set to the central portion of the thickness of the cross section of the test piece.
[0313] When the steel material is a steel strip, a steel shape, or a foil, the average chemical composition of the γ phase and the ordered phase is measured in the same manner as when the steel material is a steel plate.
[0314] <Average crystal particle size of the ordered phase>
[0315] The ordered phase is a harder phase than the γ phase, and its characteristics affect the strength of the steel. By reducing the average grain size of the ordered phase, the strength of the steel can be further improved. In particular, if the average grain size of the ordered phase is 10.00 μm or less, the strength of the steel is significantly improved.
[0316] Therefore, the average crystal grain size of the ordered phase is preferably 10.00 μm or less, more preferably 8.00 μm or less, and further preferably 5.00 μm or less.
[0317] However, from the viewpoint of feasibility of production conditions, the lower limit of the average crystal grain size of the ordered phase is, for example, 0.50 μm.
[0318] In order to set the average crystal grain size of the ordered phase to 10.00 μm or less, it is preferred that either of the following conditions (1) and (2) be satisfied.
[0319] -Condition (1)-
[0320] When cold working is performed two or more times, it is preferable to control the intermediate annealing temperature, the finish annealing temperature, the soaking holding time at the finish annealing temperature, and the degree of cold working performed between the two or more cold working times.
[0321] Specifically, the cold working degree is preferably 10% or more, the intermediate annealing temperature and the final annealing temperature are preferably 600°C to 1000°C, and the soaking holding time at the final annealing temperature preferably satisfies the following formula 3-1. If the following formula 3-1 is satisfied, the grain growth can be suppressed within an appropriate range, so that the average crystal grain size of the ordered phase becomes 10 μm or less.
[0322] Formula 3-1: (t×T) 0.5 ≥106
[0323] (In formula 3-1, t represents the soaking time of the finished product annealing (sec), and T represents the finished product annealing temperature (°C).)
[0324] -Condition (2)-
[0325] It is preferable to control the finish annealing temperature and the cold working degree. Specifically, the cold working degree and the finish annealing temperature preferably satisfy the following formula 3-2. If the following formula 3-2 is satisfied, grain growth can be suppressed within an appropriate range, so that the average crystal grain size of the ordered phase becomes 10 μm or less.
[0326] Formula 3-2: (R / T) ≥ 0.06
[0327] (In formula 3-2, R represents the degree of cold working (%), and T represents the finished product annealing temperature (°C).)
[0328] Here, the cold working degree (%) is defined by the formula: ((cross-sectional area of material before working)-(cross-sectional area of material after working)) / (cross-sectional area of material before working)×100.
[0329] In addition, the cold working degree refers to the cold rolling rate when the steel material is a steel plate, for example, and refers to the cold drawing rate when the steel material is a steel wire.
[0330] <Average crystal particle size of the ordered phase>
[0331] When the steel material is a steel plate, the average crystal grain size of the ordered phase is measured as follows.
[0332] After the L section and T section of the steel plate are mirror-polished, they are etched with a 10% oxalic acid aqueous solution to color the γ phase white and the ordered phase gray. A test piece with the polished surface as the observation surface is thus prepared. A total of 10 fields of view, including 5 or more fields of view of the L section of the steel plate and 5 fields of view of the T section, are observed. Thereafter, observation is performed with an optical microscope at a magnification of 500 times and with a scanning electron microscope at a magnification of 1000 times. When the average particle size of the ordered phase is 5.00 μm or more, the image obtained by observation with an optical microscope at a magnification of 500 times is used, and when the average particle size of the ordered phase is less than 5.00 μm, the image obtained by observation with a scanning electron microscope at a magnification of 1000 times is used.
[0333] Using the image thus obtained, the crystal grain size of the ordered phase in each field of view is calculated by the cutting method using a straight test line described in JIS G 0551:2020.
[0334] Then, the arithmetic mean value of the calculated crystal grain sizes of the ordered phase in the 10 viewing fields was calculated and was taken as the average crystal grain size of the steel material.
[0335] It should be noted that, when the steel material is a steel wire, a steel bar or a steel pipe, the average crystal grain size of the ordered phase is measured by preparing a test piece with its longitudinal section and cross section as the observation surface instead of the L section and the T section. When the steel material is a steel wire or a steel bar, the observation portion using an optical microscope or a scanning electron microscope is set to a portion corresponding to the central portion of the diameter of the steel wire or the steel bar in the cross section of the test piece. When the steel material is a steel pipe, the observation portion using an optical microscope or a scanning electron microscope is set to the central portion of the thickness of the cross section of the test piece.
[0336] When the steel material is a steel strip, a steel shape, or a foil, the average crystal grain size of the ordered phase is measured in the same manner as when the steel material is a steel plate.
[0337] <Antiphase Boundary in Ordered Phase>
[0338] Regardless of whether the ordered phase is a B2-type ordered phase or a DO3-type ordered phase, an antiphase boundary can be formed in the ordered phase. If an antiphase boundary is formed in the ordered phase, even in the ordered phase that serves as the preferred anode, especially near the antiphase boundary, it becomes a selective anode. Since the bonding force between metal atoms such as Fe that form the ordered phase and Si atoms is strong near the antiphase boundary that becomes the selective anode, metal atoms such as Fe are difficult to ionize and have better corrosion resistance. The antiphase boundary that becomes the selective anode has excellent corrosion resistance, so the corrosion resistance of the steel itself is further improved, and the formation of a passive film containing Si oxide with excellent corrosion resistance is also promoted.
[0339] Therefore, it is preferred that an anti-phase boundary be included in the ordered phase. More specifically, it is preferred that one or more anti-phase boundaries be included in one ordered phase.
[0340] It should be noted that the antiphase boundary refers to a boundary where the phase of the arrangement of atoms in the ordered phase is deviated by 180 degrees (half a period).
[0341] In order to form an anti-phase boundary in the ordered phase, it is preferred to control the finish annealing temperature, the soaking holding time at the finish annealing temperature, and the average crystal grain size of the ordered phase after the finish annealing.
[0342] Specifically, the finish annealing temperature is preferably 600 to 990° C., and the relationship between the finish annealing temperature, the soaking holding time at the finish annealing temperature, and the average grain size of the ordered phase after the finish annealing preferably satisfies the following 4 equations. If the following 4 equations are satisfied, since lattice defects such as dislocations that are the basis for the formation of the ordered phase are fully introduced into the ordered phase, an antiphase boundary is formed in the ordered phase.
[0343] 4th type: 8×10 -3 ×(T×t) 0.5 ≥d
[0344] (In formula 4, t represents the soaking time (sec), T represents the final annealing temperature (°C), and d represents the average crystal grain size of the ordered phase after final annealing.)
[0345] <Presence or absence of antiphase boundary in the ordered phase>
[0346] The presence or absence of the antiphase boundary in the ordered phase is confirmed as follows when the steel material is a steel plate.
[0347] The presence or absence of antiphase boundaries in the ordered phase was determined using a transmission electron microscope. A test piece (3 mm in diameter) was prepared by a thin film method with the thickness of the observation position set to a surface of 500 nanometers or less as the observation surface. The observation using a transmission electron microscope was performed by observing the orientation of DO3-type Fe3Si from the {002} plane.
[0348] The observation was performed at observation magnifications of 40,000 times, 80,000 times, and 400,000 times in each field of view, and a total of 10 fields of view were set. An ordered phase with an average crystal grain size of 0.5 μm or more was determined as the measurement object, and for the determined ordered phases, 10 ordered phases were selected in order from the ordered phase with the largest grain size, and the case where one or more anti-phase boundaries were confirmed in one or more ordered phases among the 10 at a magnification of 40,000 times, 80,000 times, or 400,000 times was judged to have "anti-phase boundaries in the ordered phase", and the case where no anti-phase boundary was confirmed in any of the 10 ordered phases was judged to have no "anti-phase boundary in the ordered phase".
[0349] It should be noted that, when the steel material is a wire, a rod, or a steel pipe, the confirmation of the presence or absence of an anti-phase boundary in the ordered phase is carried out by preparing a test piece (diameter 3 mm) with the polished surface as the observation surface, which is polished to a thickness of less than 100 microns relative to the cross section and then electrolytically polished to set the thickness at the observation position to less than 500 nanometers.
[0350] When the steel material is a steel strip, a steel shape, or a foil, the area ratio of the γ phase is measured in the same manner as when the steel material is a steel plate.
[0351] <Characteristics of Steel>
[0352] The product of the tensile strength and the total elongation of the steel material disclosed herein is preferably 30,000 MPa% or more, more preferably 50,000 MPa% or more.
[0353] The tensile strength of the steel material disclosed herein is preferably 1250 MPa or more, more preferably 1500 MPa or more.
[0354] The total elongation of the steel material disclosed herein is preferably 24% or more, more preferably 33% or more.
[0355] <Determination Method of Tensile Strength and Total Elongation>
[0356] When the steel material is a steel plate, a test piece cut out so that the L direction (rolling direction) becomes parallel to the stress axis is used to test the metal material tensile test method described in JIS Z 2241:2011 to measure the tensile strength (TS / MPa) and the total elongation (EL / %).
[0357] The total elongation is set to the total elongation at break in JIS Z 2241: 2011. The measurement is performed at a crosshead displacement speed of 0.002 s. -1 conditions to implement.
[0358] In addition, when the steel material is a steel wire, a steel bar, or a steel pipe, the tensile strength and the total elongation are measured by preparing a test piece cut out so that the longitudinal direction becomes parallel to the stress axis.
[0359] When the steel material is a steel strip, a steel shape, or a foil, the tensile strength and the total elongation are measured in the same manner as when the steel material is a steel plate.
[0360] <<Method for producing steel material disclosed herein>>
[0361] The manufacturing method of the steel material disclosed in the present invention may be exemplified by a manufacturing method having the following steps: a step of hot working (hot rolling, hot wire drawing, etc.) a steel billet having the average chemical composition of the steel material disclosed in the present invention to obtain a processed material; a step of annealing the processed material; a step of cold working (cold rolling, cold wire drawing, etc.) the annealed processed material; and a step of final annealing the cold-worked processed material. However, cold working and final annealing may be omitted and the hot-rolled sheet may be maintained.
[0362] The hot working is performed at a heating temperature of 900 to 1150°C, for example.
[0363] When annealing of a hot-worked material is performed, for example, it can be performed in an air atmosphere, at a soaking temperature of 600 to 1150° C., and at a soaking time of 1 to 1200 s.
[0364] Cold working is, for example, cold rolling at room temperature in an air atmosphere. Cold working may be performed multiple times, and intermediate annealing may be performed between multiple cold workings.
[0365] The finish annealing can be performed, for example, in an air atmosphere, at a soaking temperature of 600 to 1250° C., and for a soaking time of 1 to 50,000 seconds.
[0366] After the product annealing, descaling, temper rolling or shape correction using a tension leveler may be performed as needed.
[0367] The method for producing a steel material of the present disclosure can obtain a steel material having a metal structure including a γ phase and an ordered phase by processing a steel billet having the average chemical composition of the steel material of the present disclosure as described above.
[0368] Here, when the steel material is a steel plate, a steel strip, a steel shape, or a foil, the method for producing a steel material of the present disclosure performs hot rolling as hot working and performs cold rolling as cold working to produce a steel plate, a steel strip, or a foil.
[0369] When the steel material is a steel wire or a steel bar, the method for producing the steel material of the present disclosure performs hot wire drawing as hot working and performs cold wire drawing as cold working to produce the steel wire or the steel bar.
[0370] When the steel material is a welded steel pipe, the method for manufacturing the steel material disclosed herein performs hot rolling as hot working and cold rolling as cold working to obtain a steel plate or a steel strip, and then forms the steel plate or the steel strip into a tubular shape to manufacture a steel pipe. When the steel material is a seamless steel pipe, the method for manufacturing the steel material disclosed herein performs hot rolling as hot working and cold drawing as cold working to manufacture a seamless steel pipe.
[0371] In the method for producing a steel material of the present disclosure, in order to obtain the above-mentioned preferred aspects, it is preferable to produce the steel material under the above-mentioned production conditions.
[0372] <Examples of Steel Materials>
[0373] Examples of the steel material of the present disclosure include steel plates, steel strips, steel wires, steel bars, steel shapes, steel pipes, and foils.
[0374] The steel material disclosed in the present invention can be suitably used in automobile parts that require high strength, high ductility, and a high balance of strength and ductility at a level exceeding that of the current third-generation AHSS, and that require high corrosion resistance and high manufacturability.
[0375] Example
[0376] The present disclosure is not limited to the following embodiments, but can be implemented with appropriate modifications within the scope of the present disclosure, and such modifications are also included in the technical scope of the present disclosure.
[0377] The slabs having the average chemical composition shown in Table 1 were cast, and the cast slabs were hot rolled at a heating temperature of 900 to 1150° C. to obtain hot rolled sheets having a thickness of 4.0 mm. The hot rolled sheets were annealed and descaled, and then cold rolled and finished annealed under the conditions shown in Table 2. Thus, steel sheets as steel materials were obtained.
[0378] However, the annealing of the hot-rolled sheet was performed at a heating rate of 5° C. / sec and a cooling rate of 1° C. / sec. Moreover, the finish annealing of the cold-rolled sheet was performed at a heating rate of 10° C. / sec.
[0379] It should be noted that the finish annealing of the cold-rolled sheet is performed in an Ar atmosphere, but is not limited to the atmosphere.
[0380] In addition, Example 35 was set as a hot-rolled sheet without cold rolling and finish annealing of the cold-rolled sheet.
[0381]
[0382]
[0383] The manufacturability of the manufactured steel material itself was investigated. In addition, test pieces made from the steel material were used to investigate the metal structure, strength, ductility, and strength-ductility balance, and corrosion resistance.
[0384] (Investigation of Metal Structure)
[0385] Regarding the metal structure, the following properties were measured according to the above-mentioned methods.
[0386] Area ratio of γ phase
[0387] Average chemical composition of the γ phase and the ordered phase
[0388] Types and ratios of ordered phases
[0389] Average grain size of the ordered phase
[0390] ·The presence or absence of antiphase boundary in the ordered phase
[0391] Tensile strength (TS / MPa), total elongation (EL / %)
[0392] It should be noted that in the determination of the presence or absence of anti-phase boundaries in the ordered phase, the case where one or more anti-phase boundaries were confirmed in one or more ordered phases among 10 ordered phases was evaluated as YES, and the case where no anti-phase boundary was confirmed in any of the 10 ordered phases was evaluated as NO.
[0393] Furthermore, the tensile strength is used as an index of strength, the total elongation is used as an index of ductility, and the product of the tensile strength and the total elongation is used as an index of the balance between strength and ductility.
[0394] Furthermore, the mechanical properties were judged to be good if the tensile strength (TS) was 900 MPa or more, the total elongation (EL) was 22.0% or more, and the strength-ductility balance (TS×EL) was 19800 MPa·% or more.
[0395] (Corrosion resistance investigation)
[0396] The corrosion resistance was evaluated by two methods.
[0397] The first corrosion resistance evaluation method is to conduct the SST (salt spray test) test described in JIS Z 2371: 2015. After the test, the corrosion products are removed by the method described in JIS Z 2371: 2015, and then the appearance is observed, the corrosion loss is calculated, and the steel size is measured. The presence of pitting corrosion is confirmed by appearance observation, and the corrosion rate is calculated from the corrosion loss, steel density, and steel size. The case where no pitting corrosion with a diameter of 20 μm or more is confirmed and the corrosion rate is 0.1 mm / year or less is evaluated as "A (excellent)", the case where pitting corrosion with a diameter of 20 μm or more is confirmed but the corrosion rate is 0.1 mm / year or less is evaluated as "B (good)", the case where no pitting corrosion with a diameter of 20 μm or more is confirmed but the corrosion rate is 0.1 mm / year or more and 0.5 mm / year or less is evaluated as "C (acceptable)", and the case where pitting corrosion with a diameter of 20 μm or more is confirmed and the corrosion rate is 0.1 mm / year or more is evaluated as "D (unacceptable)". SST was performed in 5% neutral saline.
[0398] The second corrosion resistance evaluation method is to evaluate by the pitting potential measurement method described in JIS G 0577: 2014. The test solution is set to a 3.5 mass% sodium chloride aqueous solution, and the other measurement conditions are set as described in JIS G 0577: 2014. The pitting potential V' is measured in units of mV vs. SSE. C,100 , the corrosion resistance is evaluated by its size.
[0399] In addition, when pitting corrosion did not occur even when polarized at a potential higher than the oxygen generation potential, it was evaluated as “no pitting corrosion”.
[0400] Even if pitting corrosion occurs, the case where the pitting corrosion potential is 400 mV or more is judged to have corrosion resistance.
[0401] (Productive Investigation)
[0402] As a manufacturability inspection, the appearance of the manufactured steel material was visually checked to inspect the presence and size of cracks / fractures. The inspection range was set to an inspection range of 1 m×1 m or more including the end portion as the surface area of the steel material.
[0403] Furthermore, the case where no cracks or cracks with a length of 3 mm or more were confirmed was evaluated as "A (excellent)". In addition, the case where cracks or cracks were confirmed but the maximum length was 3 mm or more and 5 mm or less was evaluated as "B (good)", the case where the maximum length was 5 mm or more and 8 mm or less was evaluated as "C (acceptable)", and the case where the maximum length exceeded 8 mm was evaluated as "D (unacceptable)".
[0404] Table 3 shows the results of each survey.
[0405] In Table 3, the word "NO" in the column of the γ phase means "no γ phase", and the word "NO" in the column of the ordered phase means "no ordered phase".
[0406]
[0407] The above results show that the steel material of the disclosed example has high strength, high ductility, and high strength-ductility balance at a level exceeding the current third-generation AHSS, and has high corrosion resistance, compared with the steel material of the comparative example.
[0408] Furthermore, it was found that the steel material of the disclosed example suppressed cracking or fissures and had excellent manufacturability.
[0409] Here, an optical microscope photograph of the metal structure of the steel material of the present disclosure example of test number 35 after hot rolling annealing and before finish annealing (magnification 500 times, white part is γ phase, gray part is ordered phase) is shown in Figure 1 In addition, an example of an optical microscope photograph of the metal structure of the steel material of the present disclosure example of test number 36 (magnification 500 times, white part is γ phase, gray part is ordered phase) is shown in Figure 2 middle.
[0410] like Figure 1 and Figure 2 As shown in , it is known that the steel material of the disclosed example is completely different from the metal structure of the prior art. In addition, it is also known that the metal structure is refined by cold working and finish annealing.
[0411] The preferred embodiments of the present disclosure are described in detail above, but the present disclosure is not limited to the examples. Obviously, a person with ordinary knowledge in the technical field to which the present disclosure belongs can think of various changes or modifications within the scope of the technical ideas recorded in the claims, and understand that these also belong to the technical scope of the present disclosure.
Claims
1. A steel material having the following average chemical composition in terms of mass %: Ni: 18.00-36.00%, Si: 5.50-12.00%, Cu: 0-2.00%, Al:0~3.000%、 Mn: 0-2.00%, C:0~0.100%、 Cr:0~0.40% P:0~0.200%、 S:0~0.200%、 N:0~0.200%、 B:0~0.200%、 Sn: 0~0.20%, Ge: 0~0.20% Ag: 0~0.20%, Sb: 0~0.20%, Te: 0~0.20% V:0~0.200%、 Nb: 0~0.200%, Ti: 0~0.200%, Ca: 0~0.200%, Mg: 0~0.200%, Li: 0~0.20%, Sr:0~0.20%、 REM: 0~0.20% Zr:0~0.20%、 Co: 0~0.20% Mo: 0~0.20% Ta: 0~0.20%, W:0~0.20%、 PGM: 0~0.20%, Au: 0~0.20%, Re: 0~0.20%, In: 0~0.20%, Ga: 0~0.20%, Cd: 0~0.20%, Pb: 0 to 0.20%, and The rest: Fe and impurities, Furthermore, it has a metal structure including an austenite phase and an ordered phase.
2. The steel material according to claim 1, wherein: The average chemical composition of the steel material satisfies the following formula A: Type A: C+Mn / 6+Si / 24+Ni / 40+Cr / 5≤1.4 In formula A, each element symbol represents the content (mass %) of the corresponding element.
3. The steel material according to claim 1 or claim 2, wherein: The average area ratio of the austenite phase is in the range of 20 to 80%.
4. The steel material according to any one of claims 1 to 3, wherein The ordered phase includes a DO3-type ordered phase, and the ratio of the DO3-type ordered phase to all ordered phases ([DO3-type ordered phase] / [all ordered phases]) determined by X-ray diffraction satisfies the following formula B: Formula B: [DO3 type ordered phase] / [all ordered phases] ≥ 0.
20.
5. The steel material according to any one of claims 1 to 4, wherein The average chemical composition of the ordered phase satisfies the following formula C: C formula: (If ordered +Al ordered ) / (Ni ordered +With ordered )≥0.25 In formula C, the symbols of each element ordered This symbol indicates the content (mass %) of the corresponding element in the ordered phase.
6. The steel material according to any one of claims 1 to 5, wherein The average chemical composition of the austenite phase satisfies the following formula D: D type: Ni γ +0.65Cr γ +1.1Mn γ +0.4Si γ +13C γ ≥18.4 In formula D, the symbols of each element γ This symbol indicates the content (mass %) of the corresponding element in the austenite phase.
7. The steel material according to any one of claims 1 to 6, wherein The average crystal grain size of the ordered phase is 10.00 μm or less.
8. The steel material according to any one of claims 1 to 7, wherein An anti-phase boundary is contained in the ordered phase.
9. The steel material according to any one of claims 1 to 8, wherein The product of tensile strength and total elongation is 30000 MPa% or more.
10. The steel material according to any one of claims 1 to 9, wherein The tensile strength is above 1250 MPa.
11. An automobile part comprising the steel material according to any one of claims 1 to 10.
Citation Information
Patent Citations
Method for producing high strength high ductility steel sheet
JP2016141888A
Annealing process for high strength steel sheet
JP2016223003A
Hot-rolled steel products with ultra-high strength of at least 1100 MPa and good elongation of 21%
JP2020514544A